Investigation of trait anxiety as a predictor of dental anxiety - Olszewska-Czyż, Iwona; Kantorowicz, Małgorzata; Chomyszyn-Gajewska, Maria (Journal of Stomatology, 2016)
Introduction. Feeling of anxiety related to dental treatment is a fairly common phenomenon. Some studies have shown that there is an association between dental anxiety and general fears, neuroticism and general psychological disorders. Aim of the study. To examine the relationship between the dental, state and trait anxiety. Also the socio-demographic variables were considered in the study. Materials and Methods. The survey included 138 adult patients (65 women and 73 men) with the mean age (± standard deviation) of 39.3 (±14) years that were admitted to the University Dental Clinic in Cracow, Poland. The Polish version of Corah’s Dental Anxiety Scale (DAS) and State-Trait Anxiety Inventory (STAI) were used for the assessment of dental, state and trait anxiety. For statistical analysis the Cronbach’s alpha coefficient, Pearson correlation coefficient and stepwise progressive regression were applied. The cutoff level of significance was taken as p=0.05. Results. Dental anxiety was significantly correlated to the state (0.9016) and trait anxiety (0.8643). Strong relation was found between dental anxiety and the socio-demographic variables: age (0.2093), sex (0.2216), education (-0.3814) and the date of the last dental appointment (0.8134). Conclusions. Dental anxiety is related to the general tendency to be apprehensive and to manifest anxiety. It seems reasonable to manage patient’s dental anxiety symptoms properly, as this might increase their quality of life.